Access to family justice for women victims of gender violence. A perspective from the Salvadoran Law - Quintana Marxelly, Morena Guadalupe (Scientific journal of social studies, 2022)
This research exposes the theoretical foundations to incorporate gender perspective in the following essay exposes the theoretical foundations to incorporate gender perspective in the judicial process. It argues that gender analysis is a key tool to impart justice from the perspective of international and constitutional legal standards on Human Rights. It is important for the lives of women and their families. This issue is addressed from the perspective of the science of law with support of doctrinal, jurisprudential and legislative sources on human rights. The essay concludes by proposing some basic criteria in order to use gender perspective in the justice administration. In Comparative Law, good practices of applying Justice with a gender perspective are fulfilled, mostly from the jurisprudence of the Inter-American System. These suggestions, which must be taken into account in order to guarantee the due process of women’s rights towards an egalitarian society in which law and justice serve as instruments of peace for the construction of a culture of legality and protection of human rights.
Keywords: Justice; gender; equality; impunity; access to justice